HUBUNGAN PENGETAHUAN TENTANG KESEHATAN REPRODUKSI DENGAN PERILAKU PACARAN BERISIKO - Handayani, lutfi; Legina, Legina Anggraeni Syamsiar; Irwanti Gustina (Journal of Nursing and Midwifery Sciences, 2023)
Adolescence, also called puberty, is a unique transitional period characterized by various physical, emotional and psychological changes. Adolescents are in a very sensitive situation to the influence of new values, especially for those who do not have the power to resist. They tend to be easier to adjust to the flow of globalization and the free flow of information which can lead to changes in deviant behavior. The impact of social media is as follows, adolescents become addicted to using social networks without paying attention to time limits, adolescents can access freely everything on social media until adolescents are at risk of having free dating behavior in the real world. The purpose of this study was to see the relationship between knowledge about reproductive health and risky dating behavior. This type of research is descriptive using a cross sectional approach.  The population in this study was adolescents aged 15 – 19 years. in RW 01 Rawa Terate, East Jakarta, there were 75 people based on the calculation of purposive sampling. The questionnaire used in this study was the Gutman scale with univariate analysis. The results of the statistical test of the level of knowledge  of reproductive health with risky dating behavior using Chi-Square, obtained Pvalue values of 0.003 < 0.05  and Odds Ratio 5.333. Thus, it can be interpreted that there is a relationship between reproductive health knowledge and dating behavior in adolescents.  Advice for adolescents in RW 01 Rawa Terate, it is hoped that adolescents can use social media well so that they can increase knowledge related to reproductive health and avoid risky dating.